Formation of record-breaking 2015/2016 winter marine heatwave in the northwest South China Sea - Xie, Botao; Sun, Hang; Liu, Tao; Jin, Weifang; Lin, Feilong; Meng, Linxi; Wang, Yuntao (Frontiers in Marine Science, 2025)
The South China Sea (SCS) has undergone multiple marine heatwaves (MHWs) over the past few decades. Daily reanalyzed sea surface temperature (SST) data are applied to identify major MHWs in the northwest SCS over 1982–2021. The MHWs have increased in frequency, intensity, and spatial extent during recent decades, but the strongest 2015/2016 winter MHWs occurring in our study region have not been fully explained. In situ observations revealed a strong dependence of the formation of MHWs on interannual variability, i.e., the El Niño. A prominent difference in SST was identified in winters between the El Niño (2015/2016) and a normal year (2016/2017), as well as marine dynamical processes in wind and current. Due to the teleconnections of extreme El Niño, the weakened monsoon wind led to reduced basin-scale wind field anomalies and vertical currents, acting as pre-conditioning for extreme MHW events. Additionally, local oceanographic dynamics, especially upper ocean circulation and mesoscale eddies, play an important role in different MHWs during their formation and intensification by driving horizontal currents and advection. In particular, the northward flow from the tropics is favorable for the generation of MHWs. A heat budget analysis was performed, which agrees with observations, showing both enhanced solar radiation and weakened wind depressed oceanic turbulent mixing, leading to more heat being concentrated in a shallower mixed layer and resulting in the record-breaking MHW. The in situ observations offer a comprehensive insight into the formation of extreme MHWs in the SCS.